Exploring Green Finance Practices for Advancing Sustainable Development in Nepalese Banking Sector - Acharya, Swikriti; Shrestha, Sajeeb Kumar; Neupane, Dasarath; Mahat, Dipak (NPRC Journal of Multidisciplinary Research, 2024)
Background: Green finance represents a crucial strategy for promoting sustainability, emphasizing financial solutions that encourage environmentally friendly practices. Within Nepal’s banking sector, green finance initiatives are critical for addressing climate change, fostering renewable energy, and integrating sustainable development goals. Methods: A qualitative approach was adopted, employing structured interviews with nine finance managers from seven A-grade and B-grade Nepalese banks. Purposive sampling ensured relevance and depth. Data were analyzed thematically using NVivo 14 to extract key findings. Results: Key findings reveal a strong commitment to diverse green financial activities. Banks play a crucial role in financing electric mobility, promoting energy-efficient housing, and supporting renewable energy projects like hydropower. Innovative initiatives in green savings accounts, sustainable agriculture loans, and low-carbon industry financing further highlight their dedication to environmental responsibility. Conclusion: Nepalese banks are actively fostering a transition to sustainability through diverse and impactful financial products. Their collaborative efforts with government bodies and communities amplify green initiatives, supporting eco-friendly lifestyles and practices across multiple sectors. Novelty: This research uniquely maps the multifaceted role of Nepalese banks in enabling sustainable development through green finance, emphasizing innovative financial products and their tangible impact on environmental conservation and economic growth.